A Phenome-Wide Association Study of the Effects of Fusarium graminearum Transcription Factors on Fusarium Graminearum Virus 1 Infection - Yu, Jisuk; Kim, Kook-Hyung (Frontiers in Microbiology, 2021)
The Fusarium graminearum virus 1 (FgV1) causes conspicuous phenotypic changes such as reduced mycelial growth, increase pigmentation, and reduced pathogenicity in its host fungi, Fusarium graminearum. Previous study showed that the numerous F. graminearum genes including regulatory factors were differentially expressed upon FgV1 infection, however, we have limited knowledge on the effect(s) of specific transcription factor (TF) during FgV1 infection in host fungus. Using gene-deletion mutant library of 657 putative TFs in F. graminearum, we transferred FgV1 by hyphal anastomosis to screen transcription factors that might be associated with viral replication or symptom induction. FgV1-infected TF deletion mutants were divided into three groups according to the mycelial growth phenotype compare to the FgV1-infected wild-type strain (WT-VI). The FgV1-infected TF deletion mutants in Group 1 exhibited slow or weak mycelial growth compare to that of WT-VI on complete medium at 5 dpi. In contrast, Group 3 consists of virus-infected TF deletion mutants showing faster mycelial growth and mild symptom compared to that of WT-VI. The hyphal growth of FgV1-infected TF deletion mutants in Group 2 was not significantly different from that of WT-VI. We speculated that mycelial growth differences among the FgV1-infected TF deletion mutant groups might be related with the level of FgV1 RNA accumulations in infected host fungi. By conducting real-time quantitative reverse transcription polymerase chain reaction, we observed close association between FgV1 RNA accumulation and phenotypic differences of FgV1-infected TF deletion mutants in each group, i.e. increased and decreased dsRNA accumulation in Group 1 and Group 3, respectively. Taken together, our analysis provides an opportunity to identify host’s regulator(s) of FgV1-triggered signaling and antiviral responses, and helps to understand complex regulatory networks between FgV1 and F. graminearum interaction.